Antibody neutralization and its determinants in HIV-1 infected patients from Portugal: implications for vaccine design and efficacy. (29th March 2019) - Gonçalves, Patricia; Marcelino, Rute; Calado, Rita; Martin, Francisco; Gonçalves, Paloma; Janeiro, Nuno; Neno, Miguel; Afonso, Claudia; Badura, Robert; Gramacho, Filipa; Brogueira, Pedro; Mansinho, Kamal; et al.
Abstract : Introduction: Characterizing the antibody response, both neutralizing (NAb) and nonneutralizing (nNAb), in HIV-1 infected patients from Portugal may provide useful insights for vaccine design. We make the first detailed characterization of the Nab and nNAb response in Portuguese patients infected with HIV-1 and identify its determinants. Materials and methods: Plasma samples from a total of 403 patients, 372 on ART and 31 drug naïve, were analysed for neutralizing activity against a reference cross-clade Env-pseudotyped tier 2 virus panel (n = 6, subtypes B, C, AC, and CRF07_BC) and one tier one isolate (NL4.3, subtype B) in a single cycle assay in TZM-bl cells. Binding antibody activity to polypeptides comprising the C2V3C3 envelope regions from different HIV-1 clades (CRF02_AG, B, C, G and H) and peptides from a conserved region in gp41 (3S and EC262A4) was evaluated in ELISA assays. Informed consent for blood collection and study participation was obtained from all participants. The study was approved by the Ethical Boards of the Faculty of Medicine, University of Lisbon and Hospital Egas Moniz. Results: Of the 403 plasma samples tested in ELISA assays, 87.7% reacted with at least one polypeptide. The polypeptide from virus CRF02_AG was the most antigenic (61.1%) followed by H (55.1%), B (51.1%), G (50.9%), C (48.9%), 3S (12.9%) and EC262A4 (11.7%). There was a weak but significant positive correlation between the number of peptides recognized and levels of binding antibodies (r = 0.2678, p = 0.0117). Tier 1 (NL4.3) virus was neutralized by most plasma samples [87.9% (188/214) from patients on ART and 77.4% (24/31) from drug naïve patients]. Out of 39 plasma samples tested against the reference tier 2 panel of pseudoviruses, 23 (59.0%) neutralized all viruses (median 83.4% neutralization) and 14 (35.6%) neutralized between 1-5 viruses (median 48.9% neutralization). A positive correlation was observed between neutralizing potency (% of neutralization) and breadth as defined by the number of viruses neutralized (r = 0.7336, p < 0.0001). Potency of neutralization was higher in treated than in untreated patients (79.4% vs 60.2%, p < 0.0001). The virus PCH119 (clade CFR07_BC) was neutralized by most (82%) plasma samples whereas PCE1176 (clade C) was neutralized by only 61.5% of plasma samples. Discussion and conclusions: The remarkably high prevalence of HIV-1 infected individuals from Portugal with cross-clade neutralizing activity is consistent with the long-term antigenic stimulation of this population by highly diverse HIV-1 clades. Binding antibody response against the C2V3C3 envelope region is a good indicator of neutralization potency in HIV-1 infected individuals from Portugal and it may also be a good indicator of vaccine efficacy.